Diffusion of innovation in a contractor company: The impact of the social system structure on the implementation process. Issue 4 (7th October 2019) - Lundberg, Mary; Engström, Susanne; Lidelöw, Helena
Abstract : Purpose: In the construction industry, it has proven difficult to implement and realize innovation efforts, for example in the development of industrialized construction and use of platform concepts. Thus, the purpose of this study is to characterize the innovation diffusion process in the social system of a large Swedish contractor company. Specifically, the diffusion of three innovative industrialized house-building (IHB) platforms and factors affecting their adoption and implementation (particularly effects of their perceived radicality in relation to the company's decentralized characteristics) are identified and discussed. Design/methodology/approach: A case study approach was applied, using empirical material including semi-structured interviews and archival records (research reports from earlier studies at different points in time related to each innovation and annual corporate reports). The material was analyzed using Rogers' (2003) five-stage innovation process model, acknowledging the importance of social systems' structures. Findings: Structural characteristics of the social system strongly affect innovation diffusion. In subsystems that had not been involved in initiation of the innovations, they were regarded as radical, which hindered their adoption and implementation. Research limitations/implications: This study builds upon the recent findings that successful innovation implementation depends on a range of contingencies in the construction context. Although the diffusion of the innovations per se has been traced over a ten-year period, generalizability is limited because the results come from one construction company. Practical implications: Contractors have invested substantially in the development of industrialized construction and use of platform concepts, but less in their implementation, so they have obtained little gain. How innovations are perceived and implemented in different subsystems affects the success of their implementation in the overarching social system. Originality/value: This study adheres to previous calls for more research on firm level in the complex social system of construction companies by adopting a ten-year perspective on the diffusion of innovation at a large contractor addressing in particular the impact of the innovations perceived radicality in relation to the decentralized characteristics of the company.